The effect of brand image on overall satisfaction and loyalty intention in the context of color cosmetic. a pilot study. - Stephen L. Sondoh Jr; Maznah Wan Omar; Nabsiah Abdul Wahid; Ishak Ismail; Amran Harun (Penerbit Universiti Sains Malaysia, 2007)
The purpose of this study is to examine the effect of brand image benefits on satisfaction and loyalty intention in the context of color cosmetic product. Five brand image benefits consisting of functional, social, symbolic, experiential and appearance enhances were investigated. A survey carried out on 97 females showed that functional and appearance enhances significantly affect loyalty intention. Four of brand image benefits: functional, social, experiential, and appearance enhances are positively related to overall satisfaction. The results also indicated that overall satisfaction does influence customers' loyalty. The results imply that marketers should focus on brand image benefits in their effort to achieve customer loyalty.